2021
DOI: 10.1186/s13018-020-02173-9
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of infrapopliteal endovascular intervention on free flap survival in diabetic foot reconstruction?

Abstract: Background The combination of endovascular intervention and microvascular free flap transfer has been effectively used for chronic ischemic wounds of lower limb. The aim of this study was to determine the influence of angioplasty on free flap survival in diabetic foot ulcer reconstruction. Methods A retrospective research was conducted for 46 diabetic patients with chronic ulcer of the foot. All patients underwent free flap reconstruction because o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Similarly, Oh et al reported 10.212 times higher odds of flap failure in PAOD patients [ 17 ]. Nevertheless, our previous study showed the safe utilization of free flaps in PAOD patients following a successful angioplasty, particularly in cases where angioplasty achieved the complete revascularization of the pedal arch [ 18 ]. Similarly, in this study, all 21 patients with severely stenotic arteries underwent angioplasty before flap surgery, and complete flap necrosis was only seen in two cases.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Oh et al reported 10.212 times higher odds of flap failure in PAOD patients [ 17 ]. Nevertheless, our previous study showed the safe utilization of free flaps in PAOD patients following a successful angioplasty, particularly in cases where angioplasty achieved the complete revascularization of the pedal arch [ 18 ]. Similarly, in this study, all 21 patients with severely stenotic arteries underwent angioplasty before flap surgery, and complete flap necrosis was only seen in two cases.…”
Section: Discussionmentioning
confidence: 99%